PENGARUH METODE EKSPERIMEN TERHADAP HASIL BELAJAR PEMBELAJARAN IPA SISWA KELAS V SEKOLAH DASAR - Ariyanda Ariyanda; Tahmid Sabri; Suhardi Marli (Universitas Tanjungpura, 2019)
AbstractThis study aimed to analyse the influence of the Experimental Method against to students’ Learning Achievement in Science Class V Elementary School 25 North Pontianak. The material used in this research were about lighting, kinds of mirror, and optical devices. This research used Non-Equivalent Control Group Design of a quasi-experimental method. The population in this study were V Elementary class students’ of Elementary School 25 North Pontianak. The samples of this study were class VA consists of 26 experimental group students and class VB consists of 24 control group students. The technique of data collection was measurement technique using a data collector as an objective test as many as 50 question. Then the data results were tested by using t-test. Based on the analysis results obtained tcount (1,684) > ttable(1,679) so Ha is accepted . It could be concluded that there had differences between students’ learning achievement who use the experimental method with students who use the conventional learning. The calculation results effect size obtained ES of 0.34 (medium criteria). It means that learning by applying the Experimental Method give a moderate influence onstudents’learning achievement in the classV Elementary School 25 North Pontianak. Keywords: Influence, Experiment Method, Student Learning Outcomes